Catheter ablation of atrial arrhythmias following lung transplant: Electrophysiological findings and outcomes. (25th November 2020) - Mariani, Marco V.; Pothineni, Naga Venkata K.; Arkles, Jeffrey; Deo, Rajat; Frankel, David; Supple, Gregory; Garcia, Fermin; Lin, David; Hyman, Matthew C.; Kumareswaran, Ramanan; Riley, Michael; Nazarian, Saman; et al.
Abstract: Introduction: Data on the mechanisms of atrial arrhythmias (AAs) and outcomes of catheter ablation (CA) in lung transplantation (LT) patients are insufficient. We evaluated the electrophysiologic features and outcomes of CA of AAs in LT patients. Methods and Results: We conducted a retrospective study of all the LT patients who underwent CA for AAs at our institution between 2004 and 2019. A total of 15 patients (43% males, age: 61 ± 10 years) with a history of LT (60% bilateral and 40% unilateral) were identified. All patients had documented organized AA on surface electrocardiogram and seven patients also had atrial fibrillation (AF; 47% with >1 clinical arrhythmia). At electrophysiological study, 19 organized AAs were documented (48% focal and 52% macro‐re‐entrant). Focal atrial tachycardias/flutters were targeted along the pulmonary vein (PV) anastomotic site at the left inferior PV ( n = 2), ridge and carina of the left superior PV ( n = 2), left atrium (LA) posterior wall ( n = 3), LA roof ( n = 1), and tricuspid annulus ( n = 1). Macro‐re‐entrant AAs included cavotricuspid isthmus‐dependent flutter ( n = 2), incisional LA flutter ( n = 4), LA roof‐dependent flutter ( n = 1), and mitral annular flutter ( n = 3). In patients with LA mapping ( n = 13), PV reconnection on the side of the LT was found in six patients (40%, all with clinically documented AF), with a mean of 2.1 ± 0.9 PVs reconnected per patient. Patients with AF underwent successful PV isolation. After a median follow‐up of 19 months (range: 6–86 months), 75% of patients remained free from recurrent AAs. No procedural major complications occurred. Conclusion: In patients with prior LT, recurrent AAs are typically associated with substrate surrounding the surgical anastomotic lines and/or chronically reconnected PVs. CA of AAs in this population is safe and effective to achieve long‐term arrhythmia control.